2013
DOI: 10.1021/ef401760c
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular Decomposition Pathway for the Vapor-Phase Cracking of Eugenol, A Biomass Tar Compound

Abstract: To design optimal thermochemical processes for the conversion of biomass into chemicals, fuels, and electrical power, an understanding of the mechanisms for the secondary vapor-phase cracking of tar compounds is crucial. Despite the many studies examining the homogeneous secondary cracking of biomass tar existing in the literature, its thermal decomposition reaction pathways are not completely understood. Much of this lack of understanding is due to the complex, heterogeneous nature of biomass tar. A useful ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 71 publications
3
33
0
Order By: Relevance
“…Ledesma et al have discussed the mechanism of the thermal decomposition of the lignin model compound eugenol, in which they show computationally that the scission of the CÀO bond between the aromatic ring and the methoxy oxygen atom occurs with the formation of radicals. [24] Through as eries of cracking experiments,m ethanew as shown to form at temperatures above 450 8C, which supportedt he notion that the methyl radical, once formed, subsequently abstracted ahydroxyl hydrogen from eugenol. The phenoxyr adical then breaks down the arene ring by radical attack.…”
Section: Solid-state Nmr Spectroscopymentioning
confidence: 78%
“…Ledesma et al have discussed the mechanism of the thermal decomposition of the lignin model compound eugenol, in which they show computationally that the scission of the CÀO bond between the aromatic ring and the methoxy oxygen atom occurs with the formation of radicals. [24] Through as eries of cracking experiments,m ethanew as shown to form at temperatures above 450 8C, which supportedt he notion that the methyl radical, once formed, subsequently abstracted ahydroxyl hydrogen from eugenol. The phenoxyr adical then breaks down the arene ring by radical attack.…”
Section: Solid-state Nmr Spectroscopymentioning
confidence: 78%
“…which can be signicant in the production of many specialty or platform chemicals. There has been a very few experimental studies 8,[12][13][14]24,25 on eugenol as the bio-oil model compound and only a single combined, i.e., both experimental and computational study 25 of eugenol as the bio-oil model compound is available in the literature to the best of authors' knowledge. For instance, Nimmanwudipong et al 13 carried out conversion reactions of eugenol in the presence of Pt/g-Al 2 O 3 and HY zeolite catalysts; and reported various products, e.g., phenol, guaiacol, veratrole, 4-propylguaiacol, 4-propylphenol, p-cresol, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al 8 carried out hydrodeoxygenation of eugenol over carbon nanotube (CNT) supported ruthenium catalyst and reported propylcyclohexane as nal alkane product with 4-propylguaiacol and 4-propylcyclohexanol as intermediate products. A combined study of eugenol decomposition in vapour phase carried out by Ledesma et al 25 and they reported methane, ethylene, acetylene, propylene, benzene, CO, and 1-butene as the major products.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations